Контроль часу в управлінні виробництвом - Артеменко, А. Д. (ХНУРЕ, 2024)
Discusses the importance of systematically monitoring and accurately determining lead times at each stage of order production in a modern manufacturing environment. The importance of mandatory checks for possible defects or deficiencies after each stage is emphasized. The integration of information systems to optimize production and ensure product quality is considered. The ConWIP (Constant Work-In-Process) method is highlighted as an effective tool for increasing production productivity and efficiency. Examines how implementing status updates at each stage, alongside ConWIP, can lead to more precise lead time calculations and overall improved production planning.
Keywords: моніторинг часу; управління завданнями; облік виробничих процесів; планування графіків; аналітика продуктивності